7-Chloro-4-aminoquinoline γ-hydroxy-γ-lactam derived-tetramates as a new family of antimalarial compounds. Issue 21 (1st November 2016) - Chopin, Nicolas; Iikawa, Shinya; Bosson, Julien; Lavoignat, Adeline; Bonnot, Guillaume; Bienvenu, Anne-Lise; Picot, Stéphane; Bouillon, Jean-Philippe; Médebielle, Maurice
Graphical abstract: Abstract: In this Letter we report on an efficient and short 2–3 steps synthesis of γ-hydroxy-γ-lactam derived-tetramates bearing a 7-chloro-4-aminoquinoline skeleton and their evaluation as potent antimalarials. These molecules were obtained through ring opening-ring closure (RORC) process of γ-ylidene-tetronate derivatives in the presence of 7-chloro-4-aminoquinoline-derived amines. In vitro antimalarial activity of these new γ-lactams was evaluated against Plasmodium falciparum clones of variable sensitivity (3D7 and W2) and they were found to be active in the range of 14–827 nM with generally good resistance index. A preliminary SAR study is also presented to explain these results. Finally, the most active compounds did not show in vitro cytotoxicity when tested against Human Umbilical Vein Endothelial Cells (HUVEC) up to concentration of 50 μM and they were stable at pH 7.4 for at least 48 h.